Heat-driven ejector refrigeration system for hot-spring resorts application - Espeña, Glen D. (College of Engineering, University of the Philippines Diliman, 2014)
The heat-driven ejector refrigeration system offers the advantage of simplicity and operates from low-temperature heat energy sources, thereby, it proves to be a good substitute to the conventional compressor-driven refrigeration system when any or combination of the heat source is available. Both systems perform the same cooling function but differ in their energy sources. The former employs renewable heat sources such as solar-thermal. Geothermal, biomass and industrial or commercial waste heat sources to power up the system, while the later utilizes the more costly electricity. In addition, the ejector system can use CFC free and environment-friendly refrigerants for the system to operate thus curtailing the hazardous effects on the environment. In this paper, a mathematical model is developed using R 134a, R 152a, and R 1270 to determine the ejector geometries based on the properties and state conditions of the refrigerant entering and leaving the ejector. Additionally, a 450 W ejector chiller design is created for boiler temperature range of 70 deg C to 110 degC; 25 degC to 45 degC condenser temperature and 0 degC to 10 degC evaporator temperature. The ejector efficiency varied from 0.94 to 0.99. The research discusses its direct-use application on the utilization of geothermal energy for hot spring resorts. A heat-driven ejector refrigeration system is designed to supply the cooling and refrigeration requirements of hot spring establishments. The study has established a novel way to effectively utilize hot spring water into useful and economical cooling through the ejector refrigeration system